Parental Role in Instilling Moral Values in Early Childhood During the Digital Era: A Case Study of a Muslim Family - Filla, Silvia Anggery; Afrianto, Afrianto; Murni, Emilza Tri; Indria, Anita (Al-kayyis: Journal of Islamic Education, 2025)
This study aims to examine the role of parents in instilling moral values in early childhood in the digital age. The phenomenon of increasing exposure to digital content that has the potential to disrupt children's character development is the main background of this study. Children tend to imitate behavior from digital media, while some parents, despite being highly educated, do not provide direct moral guidance due to their busy schedules or the assumption that moral education will be obtained from school and the environment. This study uses a qualitative approach with a case study method, involving observation, interviews, and documentation as data collection techniques. The analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that active parental involvement has a significant effect on three main aspects of children's moral development: psychological condition, temperament, and empathy. Children who receive attention and moral guidance from their parents tend to have better self-confidence, are able to control their emotions, and show concern for others. The implications of this study emphasize the importance of the role of parents as primary educators in shaping children's character amid the challenges of the digital age, as well as the need to increase parents' awareness and capacity to carry out this function consistently.